2012
DOI: 10.1189/jlb.0911465
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid-derived suppressor cells from tumor-bearing mice impair TGF-β-induced differentiation of CD4+CD25+FoxP3+ Tregs from CD4+CD25−FoxP3− T cells

Abstract: MDSCs and Tregs play an essential role in the immunosuppressive networks that contribute to tumor-immune evasion. The mechanisms by which tumors promote the expansion and/or function of these suppressive cells and the cross-talk between MDSC and Treg remain incompletely defined. Previous reports have suggested that MDSC may contribute to Treg induction in cancer. Herein, we provide evidence that tumor-induced gr-MDSCs, endowed with the potential of suppressing conventional T Lc, surprisingly impair TGF-β1-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 57 publications
3
60
1
Order By: Relevance
“…In addition, studies have shown that TGFb plays an important role in the biological function of MDSCs. 39,40 Here, we found that TGFb levels were increased in the cell culture supernatant when TW03 and T-MDSCs were co-cultured but were significantly decreased in the supernatant when TW03 and T-MDSCs were co-cultured with a transwell insert, as shown in Fig. S3.…”
Section: T-mdscs Induce Cancer Cell Emt By Cell-to-cell Contact In Vitromentioning
confidence: 68%
“…In addition, studies have shown that TGFb plays an important role in the biological function of MDSCs. 39,40 Here, we found that TGFb levels were increased in the cell culture supernatant when TW03 and T-MDSCs were co-cultured but were significantly decreased in the supernatant when TW03 and T-MDSCs were co-cultured with a transwell insert, as shown in Fig. S3.…”
Section: T-mdscs Induce Cancer Cell Emt By Cell-to-cell Contact In Vitromentioning
confidence: 68%
“…Alternatively, PMN-MDSCs could interfere with Treg homeostasis in vivo as recently demonstrated in murine cancer studies. 43 Nevertheless, our data indicates that FOXP3-expressing T cells and Th17 cells differ substantially in their longitudinal ECP response characteristics, suggesting that further in-depth T-cell phenotyping is required to fully understand the effects of ECP on T-cell homeostasis. Although percentages of PMN-MDSCs increased significantly upon ECP treatment, absolute numbers increased only tendentially, but not in a statistically significant manner (Supplementary Figure 11).…”
Section: Discussionmentioning
confidence: 93%
“…25 The serum concentration of TGF-b1 and the percentage of intratumoral CD4 C CD25 C Foxp3 C regulatory T (Treg) cells were decreased in captopril-treated tumor-bearing mice (Fig. S5).…”
Section: Acei Polarizes Splenic Neutrophils Toward An Antitumor Phenomentioning
confidence: 99%
“…Splenic neutrophils were isolated from either control tumor-bearing mice or captopril (50 mg/kg/ d)-treated tumor-bearing mice, and exposed to CD4 C CD25 ¡ lymphocytes with anti-CD3, anti-CD28, IL-2, and TGF-b1 as previously described. 25 Since neutrophils are dying cells and the half-life of neutrophils with ex vivo manipulation is thought to be less than 24 h, 26 we examined the effect of Ly6G C cells on iTreg induction within Ly6G C cells from control tumor-bearing mice or captopril-treated tumor-bearing mice were isolated and exposed to 4T1 cells at a ratio of 10:1 for 18 h. (E) Effects of captopril on Ly6G C cells from naive mice. Blood, bone marrow, and splenic Ly6G C cells were isolated from naive mice and exposed to 500 mM captopril for 4 h, and then mean lobe counts were measured.…”
Section: Acei Polarizes Splenic Neutrophils Toward An Antitumor Phenomentioning
confidence: 99%